Tinjauan Hukum Kewenangan Sistem TRUST +POSITIFâ„¢ sebagai Database Acuan dan Rujukan Penyaringan Seluruh Layanan Akses Informasi Publik Penggunaan Internet di Indonesia - Christian Andersen (Dialogia Iuridica, 2017)
The implementation of good governance become the main agenda that has to be done by any government agencies. Because this is a requirement that shows the Government's commitment in carrying out theirs duty to serve the community. All officers must have an understanding of public information disclosure / Keterbukaan Informasi Publik (KIP) based on Act Number 14 of 2008, the principles which referred to is accountability, transparency and the supremacy of law. This article is a normative legal research studying the principles/laws that is a research on applied regulations related to The Implementation of Trust +Positif Concerning Good Governance. This research aims to reveal the regulations related to the implementation of community service in conducting good governance in order to prepare ASEAN Economic Community. The conclusion of this research are that to create a good governance as expected by the community, the implementation of the function of Trust +Positif service is needed and we have to create synergy between the governmental officers who implement the policy and the community whom the policy applied to. Therefore, it is necessary to have cooperation between the two parties.